3
$\begingroup$

Let $X_i \sim^{iid} F$ for $i=1,...,n$, where $F$ is a continuous distribution.

I want to find the pdf for $X_{(1)},X_{(2)},..., X_{(r)}$, with $r\leq n$.

We know that $f_{X_{(1)},X_{(2)},..., X_{(n)}}=n!\prod^n_{i=1}f(x_{(i)})$, when $x_{(1)}\leq x_{(2)}\leq \cdots\leq x_{(n)}$; $f_{X_{(1)},X_{(2)},..., X_{(n)}}=0$ otherwise.

Well when integrating

$$f_{X_{(1)},X_{(2)},..., X_{(r)}}=n! \prod^r_{i=1}f(x_{(i)}) \int^{\infty}_{x_{(r)}}\cdots \int^{\infty}_{x_{(n-1)}}f(x_{(n)})\cdots f(x_{(r+1)})dx_{(n)}\cdots dx_{(r+1)} $$

$$=n! \prod^r_{i=1}f(x_{(i)}) \int^{\infty}_{x_{(r)}}\cdots \int^{\infty}_{x_{(n-2)}}(1-F(x_{(n-1)})) f(x_{(n-1)}) \cdots f(x_{(r+1)})dx_{(n-1)}\cdots dx_{(r+1)}$$

$$=n! \prod^r_{i=1}f(x_{(i)}) \int^{\infty}_{x_{(r)}}\cdots \int^{\infty}_{x_{(n-3)}}\frac{-(1-F(x_{(n-2)}))^2}{2} f(x_{(n-2)}) \cdots f(x_{(r+1)})dx_{(n-2)}\cdots dx_{(r+1)}$$

and reaching at the end $$f_{X_{(1)},X_{(2)},..., X_{(r)}}=n! (-1)^{n-r}\frac{(1-F(x_{(r)}))^{n-r-1}}{(n-r-1)!} \prod^r_{i=1}f(x_{(i)}) $$

This doesn't seem to be correct, since we have that annoying -1 factor. Where did I go wrong?

$\endgroup$
  • 2
    $\begingroup$ The $-1$ was never there. Go back to the second integral and notice it had to be evaluated between $x_{(n-2)}$ and $\infty$. It's zero at the upper limit and the value at the lower limit has to be subtracted, yielding $(1-F(x_{(n-2)})^2/2$ rather than its negative. $\endgroup$ – whuber Jul 26 '14 at 17:35
5
$\begingroup$

From @whuber,

$\int^{\infty}_{x_{(n-2)}}(1-F(x_{(n-1)})) f(x_{(n-1)})dx_{(n-1)}=\left[-\frac{(1-F(x_{(n-1)}))^2}{2}\right]_{x_{(n-2)}}^{\infty}=0+\frac{(1-F(x_{(n-2)}))^2}{2}$

$\endgroup$
  • $\begingroup$ Is the end result then: $$f_{X_{(1)},X_{(2)},..., X_{(r)}}=n! \frac{(1-F(x_{(r)}))^{n-r-1}}{(n-r-1)!} \prod^r_{i=1}f(x_{(i)}) $$ ? $\endgroup$ – axk Jan 29 '18 at 19:59
  • $\begingroup$ @axk Yes, I think so. $\endgroup$ – An old man in the sea. Jan 29 '18 at 21:14
  • $\begingroup$ But then for $r=n$ how do we get rid of the fraction? $\endgroup$ – axk Jan 29 '18 at 21:20
  • $\begingroup$ @axk It's written on the original question. The derivation is for when $r\leq n-1$. For $r=n$ it's already known. $\endgroup$ – An old man in the sea. Jan 30 '18 at 10:21
  • $\begingroup$ The question sais $r\le n$. This is what I don't understand: For the case $r=n-1$ the formula gives what is known for the case $r=n$, and for the case $r=n$ it doesn't. $\endgroup$ – axk Jan 31 '18 at 1:29
1
$\begingroup$

The end result should be $$f_{X_{(1)},X_{(2)},..., X_{(r)}}=n! \frac{(1-F(x_{(r)}))^{n-r}}{(n-r)!} \prod^r_{i=1}f(x_{(i)}) $$

...by the same approach as on page 9 of this book https://books.google.co.uk/books/about/Order_Statistics_and_Inference.html?id=chvvAAAAMAAJ by N. Balakrishnan, A. Clifford Cohen (we get it directly by using only the third of the integrals in their derivation of joint density of 2 order statistics, i.e. using eq. (2.3.4))

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.